18 Rare disease manifestations in SLE. (1st September 2020) - Amoura, Zahir; Furie, Richard; Isenberg, David
Abstract : Case 1: A 20-year-old female with SLE and myocarditis: Zahir Amoura: A 20-year-old female with systemic lupus erythematosus (SLE) was referred for chest pain and skin lesions. The diagnosis of SLE was made 4 years earlier, when she developed arthritis, proteinuria, with positive antinuclear antibodies (1/1280), anti-dsDNA, anti-SS-A, and anti-Sm antibodies. The renal biopsy showed Class I lupus nephritis. The patient was treated with low-dose steroids and hydroxychloroquine. One year later, she had pulmonary embolism and received warfarin because of the presence of persistent lupus anticoagulant. Two months before admission, while the patient was receiving hydroxychloroquine (400 mg/day), hand skin lesions gradually developed. At admission, the patient complained of chest pain and went to the emergency department. Her temperature was 36.6°C, blood pressure 130/70 mmHg, pulse rate 90 beats per minute, respiration rate 18 breaths/minute, and oxygen saturation 98% while she was breathing ambient air. There was normal breath sounds in the lungs' fields. Laboratory tests showed hemoglobin 10.3 g/dL, lymphocytes 0.9 G/L, normal platelets, international normalised ratio (INR) for prothrombin time 2.3, creatinine 69 μmol/L, elevated ultrasensitive troponin T (248 ng/L), low C3 (0.55 mg/dL), positive anti-dsDNA antibodies (45 U/mL) and proteinuria 1.5 g/24h. Serum protein electrophoresis showed a normal pattern and a diffuse increase in immune globulin. The tests for lupus anticoagulant, anticardiolipin antibodies, were positive. Discussion Point: Diagnosis and management of lupus myocarditis Learning Objectives: Describe the clinical presentation of lupus myocarditis Discuss the diagnosis workshop for lupus myocarditis Discuss treatment options of lupus myocarditis Case 2: A 22-year-old male with thrombotic microangiopathy: Richard Furie: A 22-year-old male was admitted to the hospital because of headache, confusion and fever. He had been previously well. At the time of admission, he was on no medications. Initial laboratory test results were notable for WBC 2, 800, Hb: 6.7; platelets: 64, 000 and creatinine: 1.9. The patient was given broad spectrum antibiotics for the treatment of sepsis and/or bacterial meningitis. However, the patient's mental status worsened and he became comatose. All cultures were sterile. A 'shotgun' diagnostic approach revealed ANA 1/2560 (H) and DNA 883 IU/dL. The creatinine continued to rise. The impression was that of SLE complicated by anemia, thrombocytopenia, nephropathy and CNS disease. 'Pulse' steroids were administered for 3 days without subsequent improvement. Intravenous gamma-globulin failed to raise the platelet count. Rheumatology to the rescue! Discussion Point: Diagnosis and management of thrombotic microangiopathy (TMA) Learning Objectives: Describe the clinical presentation of TMA Discuss treatment options of TMA Review proposed modifications to the classification of lupus nephritis